A New Method of Insulation Wire for Power Transformers - Khalaf Y. Al-Zyoud (Institute of Advanced Engineering and Science, 2017)
This task go in order to developing a new way of enameled and polyester foil insulation of conductors used in building transformers thermal of class temperature about (150 ℃), the production technology for two types of enameled and polyester foil-insulation conduction are presented. As will as the physical, mechanical and electrical characteristics of conductors in a normal climate N2, in a tropical climate T2 and after 28 cycle at ( 200 ℃ ) are presented.